CLIMATE CHANGE IN BELARUS. SOCIAL AND ECONOMIC RISKS AND PROSPECTS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article deals with some issues of climate shift and its impact on the development of the economy and civil society in Belarus at the present stage. In particular, the following areas have been highlighted and discussed: the impact of climate change as a whole on the global community, as well as social and economic consequences. The development of the Republic of Belarus under the conditions of climate transformation in such spheres as agriculture, energy, and tourism was analyzed. The contribution of the republic to the reduction of total greenhouse gas emissions is emphasized.
Keywords: climate change; Belarus; social and economic consequences